Tumor site-directed A1R expression enhances CAR T cell function and improves efficacy against solid tumors - Kevin Sek; Amanda X. Y. Chen; Thomas Cole; Jesse D. Armitage; Junming Tong; Kah Min Yap; Isabelle Munoz; Phoebe A. Dunbar; Shiyi Wu; Marit J. van Elsas; Olivia Hidajat; Christina Scheffler; et al. (Nature Communications)
Abstract The efficacy of Chimeric Antigen Receptor T cells against solid tumors is limited by immunosuppressive factors in the tumor microenvironment including adenosine, which suppresses Chimeric Antigen Receptor T cells through activation of the A2A receptor. To overcome this, Chimeric Antigen Receptor T cells are engineered to express A1 receptor, a receptor that signals inversely to A2A receptor. Using murine and human Chimeric Antigen Receptor T cells, constitutive A1 receptor overexpression significantly enhances Chimeric Antigen Receptor T cell effector function albeit at the expense of Chimeric Antigen Receptor T cell persistence. Through a CRISPR/Cas9 homology directed repair “knock-in” approach we demonstrate that Chimeric Antigen Receptor T cells engineered to express A1 receptor in a tumor-localized manner, enhances anti-tumor therapeutic efficacy. This is dependent on the transcription factor IRF8 and is transcriptionally unique when compared to A2A receptor deletion. This data provides a novel approach for enhancing Chimeric Antigen Receptor T cell efficacy in solid tumors and provides proof of principle for site-directed expression of factors that promote effector T cell differentiation.